Combination of the Endogenous lhcsr1 Promoter and Codon Usage Optimization Boosts Protein Expression in the Moss Physcomitrella patens - Hiss, Manuel; Schneider, Lucas; Grosche, Christopher; Barth, Melanie A.; Neu, Christina; Symeonidi, Aikaterini; Ullrich, Kristian K.; Perroud, Pierre-François; Schallenberg-Rüdinger, Mareike; Rensing, Stefan A. (Frontiers in Plant Science, 2017)
The moss Physcomitrella patens is used both as an evo-devo model and biotechnological production system for metabolites and pharmaceuticals. Strong in vivo expression of genes of interest is important for production of recombinant proteins, e.g. selectable markers, fluorescent proteins or enzymes. In this regard, the choice of the promoter sequence as well as codon usage optimization are two important inside factors to consider in order to obtain optimum protein accumulation level. To reliably quantify fluorescence we transfected protoplasts with promoter:GFP fusion constructs and measured fluorescence intensity of living protoplasts in a plate reader system. We used the red fluorescent protein mCherry under 2x 35S promoter control as second reporter to normalize for different transfection efficiencies. We derived a novel endogenous promoter and compared deletion variants with exogenous promoters. We used different codon-adapted green fluorescent protein (GFP) genes to evaluate the influence of promoter choice and codon optimization on protein accumulation in P. patens, and show that the promoter of the gene of P. patens chlorophyll a/b binding protein LHCSR1 drives expression of GFP in protoplasts significantly (more than 2-fold) better than the commonly used 2x 35S promoter or the rice actin1 promoter. We identified a shortened 677 bp version of the lhcsr1 promoter that retains full activity in protoplasts. The codon optimized GFP yields significantly (more than 2-fold) stronger fluorescence signals and thus demonstrates that adjusting codon usage in P. patens can increase expression strength. In combination, new promotor and codon optimized GFP conveyed 6-fold increases fluorescence signal.